2021
DOI: 10.21037/gs-21-406
|View full text |Cite
|
Sign up to set email alerts
|

ROBO1 protein expression is independently associated with biochemical recurrence in prostate cancer patients who underwent radical prostatectomy in Asian patients

Abstract: Background: The purpose of this study is to investigate the correlation between ROBO1 expression and prostate cancer aggressiveness Methods: ROBO1 expression was evaluated in normal prostate epithelial cells (PrEC) and different prostate cancer cell lines by Western blot analysis. The migration and invasion of native and ROBO1 knockdown cells were evaluated using migration chambers and a Matrigel-coated membrane, respectively. Samples from 145 patients who underwent radical prostatectomy between June 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…ROBO1 is highly expressed in the PCa cell lines. All ROBO1 knockdown cells (PC3, 22Rv1, and DU 145) showed markedly decreased migration and invasiveness compared to native cells [27]. LUZP2, a gene encoding leucine zipper protein 2, is located at 11p14.3 and is primarily expressed in the brain tissue and prostate, which was rarely studied in the field of oncology before, and its downregulation is associated with senescence [28].…”
Section: Discussionmentioning
confidence: 99%
“…ROBO1 is highly expressed in the PCa cell lines. All ROBO1 knockdown cells (PC3, 22Rv1, and DU 145) showed markedly decreased migration and invasiveness compared to native cells [27]. LUZP2, a gene encoding leucine zipper protein 2, is located at 11p14.3 and is primarily expressed in the brain tissue and prostate, which was rarely studied in the field of oncology before, and its downregulation is associated with senescence [28].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive genomic study has identified Robo1 gene mutations in SCLC patients [ 29 ]. Genetic and immunological inhibition of Robo1 has established its oncogenic role in multiple myeloma and prostate cancer in vitro and in vivo [ 30 , 31 , 32 ]. Genetic suppression of Slit2 or overexpression of Robo1 in hepatocellular carcinoma promotes tumor growth and metastasis [ 33 ].…”
Section: Introductionmentioning
confidence: 99%